2018
DOI: 10.1186/s12888-018-1795-7
|View full text |Cite
|
Sign up to set email alerts
|

A new device-aided cognitive function test, User eXperience-Trail Making Test (UX-TMT), sensitively detects neuropsychological performance in patients with dementia and Parkinson’s disease

Abstract: BackgroundA newer generation neuropsychological tests can take advantage of touch screen and mobile technology. We have developed a new Android application termed “User eXperience-Trail Making Test (UX-TMT)” for neurocognitive assessment and training. This study investigated the utility, including the reliability and the validity, of the UX-TMT as a screening test for cognitive decline in adults.MethodsA total of 84 individuals aged 27–86 years were divided into three groups; healthy controls ([HC] n = 29), pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
(58 reference statements)
0
21
0
Order By: Relevance
“…Thirteen articles described new tests that took advantage of the mobile platform. Five discussed short tests for mass screening (Brouillette et al, 2013; Onoda et al, 2013; Onoda & Yamaguchi, 2014; Possin et al, 2018; Scanlon et al, 2016), five discussed test batteries covering several domains of cognitive function (Freedman et al, 2018; Kokubo et al, 2018; Makizako et al, 2013; Rentz et al, 2016; Zorluoglu et al, 2015), and three described tests designed for repeated administration (Allard et al, 2014; Jongstra et al, 2017; Lange & Suss, 2014). Screening tests require a relatively short time to complete and focus on general cognitive function or a few specific domains known to change in the early stages of cognitive decline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirteen articles described new tests that took advantage of the mobile platform. Five discussed short tests for mass screening (Brouillette et al, 2013; Onoda et al, 2013; Onoda & Yamaguchi, 2014; Possin et al, 2018; Scanlon et al, 2016), five discussed test batteries covering several domains of cognitive function (Freedman et al, 2018; Kokubo et al, 2018; Makizako et al, 2013; Rentz et al, 2016; Zorluoglu et al, 2015), and three described tests designed for repeated administration (Allard et al, 2014; Jongstra et al, 2017; Lange & Suss, 2014). Screening tests require a relatively short time to complete and focus on general cognitive function or a few specific domains known to change in the early stages of cognitive decline.…”
Section: Resultsmentioning
confidence: 99%
“…The User eXperience-Trail Making Test (UX-TMT) was developed for cognitive assessment and training (Kokubo et al, 2018). The UX-TMT consists of neurocognitive assessment, cognitive training, and life-logging.…”
Section: Resultsmentioning
confidence: 99%
“…In the Trails Test, PD patients also needed more time and committed more errors than controls. Although several previous studies reported deficits on the TMT in PD ( Muslimoviæ et al, 2005 ; Colman et al, 2009 ; Godefroy et al, 2010 ; Dirnberger and Jahanshahi, 2013 ; Kourtidou et al, 2015 ; Hessen et al, 2016 ; Vlagsma et al, 2017 ; Hoogland et al, 2018 ), other studies reported no difference between PD and controls ( Bouquet et al, 2003 ; Kokubo et al, 2018 ), even in PD patients with ICD ( MacK et al, 2013 ). Cools et al (2001) have argued that impairment in task-set switching only appears when competing information is present, i.e., when the load on selection mechanisms increases.…”
Section: Discussionmentioning
confidence: 85%
“…Besides digital CDT, some other digital drawing tests have been suggested in the literature. The digital pentagon drawing test (Garre-Olmo et al, 2017;Tsoi et al, 2018) and digital ROCF (Cheah et al, 2019;Kokubo et al, 2018) are adapted from paper-and-pencil versions.…”
Section: Discussionmentioning
confidence: 99%